Siegfried Kracauer : an introduction - Koch, Gertrud, 1949- (Princeton University Press, 2000)
"Gertrud Koch has written a most lucid and much-needed analytical introduction to the diverse work of Siegfried Kracauer. Her study is brief yet comprehensive, both precise and incisive, deferent to previous scholarship yet never derivative. Koch's book is decidedly original in its sensitivity to recurrent metaphors (especially spatial images) that provide crucial points of orientation and focus throughout Kracauer's complex oeuvre."--Eric Rentschler, Harvard University "Gertrud Koch's probing, sensitive, and demanding study of the work of Siegfried Kracauer is the first such sustained analysis of the wide range of Kracauer's writings in any language. The book represents the state of the art of scholarship on Kracauer, fully conversant with the extensive published works, the fascinating unpublished archival holdings in Marbach, and the wide range of secondary Kracauer literature in both German and English."--Thomas Y. Levin, Princeton University